Estimating the requirement for manipulation of medicines to provide accurate doses for children. Issue 1 (12th September 2012) - Nunn, Anthony; Richey, Roberta; Shah, Utpal; Barker, Catrin; Craig, Jean; Peak, Matthew; Ford, James; Turner, Mark
Abstract : Objective: To determine the type and frequency of manipulations of drug dosage forms required to administer smaller doses for children and the drugs involved. Methods: An experienced paediatric clinical pharmacist estimated the requirement to manipulate a medicine to achieve accurate dose administration from prescription data in all neonatal and paediatric inpatients collected over 5-day periods and information on drug dosage form availability in a regional children's hospital (RCH) and regional paediatric intensive care unit (RPICU), a regional neonatal intensive care unit (RNICU) and paediatric and neonatal wards of a district general hospital (DGH) using paper-based prescribing systems. Doses were expressed by weight. Ward stock supply with some intravenous drugs ready-to-administer was provided. The main outcome measures were the estimated requirement for dosage form manipulation, nature of the manipulation and drug name. Results: Of 5375 evaluated drug administrations, 542 (10.1%) were judged to require manipulation or measurement of a small volume (<0.2 ml). The most frequent manipulation was measurement of oral dose in volumes of 0.1 to <0.2 ml in the DGH. Requirement to measure doses of <0.1 ml (oral and intravenous) accounted for 25.2% of all manipulations, with the need to measure intravenous doses of <0.1 ml being most frequent in the RNICU and RPICU (60.4% and 31.9% of manipulations, respectively). Hydrocortisone was the drug most frequently judged to require manipulation with both measurement of small volumes for intravenous injection (RPICU and RNICU) and segmentation of tablets (RCH). Conclusions: Manipulation of medicines (including measurement of very small volumes) to provide accurate smaller doses for children is common in the hospital setting.